Influence of Sulfide Concentration on the Properties of Cr3C2-25(Ni20Cr) Cermet Coating on Al7075 Substrate - Mieczyslaw Scendo (Metals)
The influence of sulfide (S2−) concentration on the corrosion resistance of Cr3C2-25(Ni20Cr) cermet coating on Al7075 (EN, AW-7075) substrate (Cr3C2-25(Ni20Cr)/Al7075) was investigated. The coating was produced by the cold-sprayed (CS) method. The Cr3C2-25(Ni20Cr)/Al7075 coatings were modified chemically in solutions containing thioacetic acid amide (TAA). The surface and microstructure of the specimens were both observed by a scanning electron microscope (SEM). The mechanical properties of the Cr3C2-25(Ni20Cr) coatings were characterized using microhardness (HV) measurements. The corrosion tests of the materials were carried out using the electrochemical method in a acidic chloride solution. The adsorbed (MemSn)ads layer effectively separates the Cr3C2-25(Ni20Cr)/Al7075 coating surface from contact with the aggressive corrosive environment. More than a twice lower value of corrosion rate (CW) was obtained for the Cr3C2-25(Ni20Cr)/Al7075 coating after exposure to the environment with 0.15 M TAA.